Effect of rTMS intervention on upper limb motor function after stroke: A study based on fNIRS - Ni, Jing; Jiang, Wei; Gong, Xueyang; Fan, Yingjie; Qiu, Hao; Dou, Jiaming; Zhang, Juan; Wang, Hongxing; Li, Chunguang; Su, Min (Frontiers in Aging Neuroscience, 2023)
This study has evaluated the effects of different rTMS stimulation programs on upper limb function and corresponding brain functional network characteristics of patients with stroke and sought a new objective standard based on changes in brain network parameters to guide accurate rTMS stimulation programs. Results:1. Before treatment, there was no statistical difference in Fugl-Meyer score between the control group and the magnetic stimulation group (P=0.178).FMA scores increased faster in the magnetic stimulation group at 2 and 4 weeks compared with the control group at the same time point (P＜0.001).TMS1 and TMS2 were compared at the same time point, FMA score in TMS2 group increased more significantly after 4 weeks of treatment (P=0.010).2. Before treatment, HbO2 content in healthy sensory motor cortex (SMC) area of magnetic stimulation group and control group was higher than that in other region of interest (ROI) area, but there was no significant difference in ROI between the two groups. After 4 weeks of treatment, the HbO2 content in the healthy SMC area was significantly decreased (P＜0.001), while the HbO2 content in the affected SMC area was significantly increased, and the change was more significant in the magnetic stimulation group (P＜0.001).3.TMS2 group was more advantageous than TMS1 group in improving the mean increment of brain network parameters. Conclusions:1. The rTMS treatment is beneficial to the recovery of upper limb motor function in stroke patients .and can significantly improve the intensity of brain network connection and reduce the island area. The island area refers to an isolated activated brain area that cannot transmit excitation to other related brain areas. 2. When the node degree of M1_Healthy region less than 0.52, it is suggested to perform promotion therapy only in the affected hemisphere. while the node degree greater than 0.52, and much larger than that in the M1_affected region. it is suggested that both inhibition in the healthy hemisphere and high-frequency excitatory magnetic stimulation in the affected hemisphere can be performed. 3. In different brain functional network connection states, corresponding adjustment should be made to the treatment plan of rTMS to achieve optimal therapeutic effect and precise rehabilitation treatment.